Singapore in the Malay world [ building and breaching regional bridges - Rahim, Lily Zubaidah , 1960- (Asia's transformations, 2009)
Reflecting on Singapore's policy of meritocratic multiracialism and the communalist state of Malay, this book examines the way by which these policies, coupled with historical animosities, competitive economic tensions and janus-faced foreign economic policy orientation have contributed to Singapore's mercurial relations with Malaysia